Isolation and purification of copeptin hormone from serum of patients with heart disease - Thikra Ali Allwsh; Noori Mohammed Aziz (Tikrit Journal of Pure Science)
This study included isolation and purification of copepin hormone from heart disease patients serum using different biochemical techniques. The study showed two proteinous peak has been isolated by gel filtration (Sephadex G-50) from the precipitation by cold acetone, the results predicted that (peak B) has a high concentration of copepin . Furthermore, the purity of the isolated copeptin ( peak B) had been identified by SDS-poly acryl amide gel electrophoresis and the reverse phase high performance liquid chromatography in which results showed agood identity in retention time between the standard and the isolated copeptin (peak B) .